Environmental and nutrition impact of achieving new School Food Plan recommendations in the primary school meals sector in England. Issue 4 (5th April 2017) - Wickramasinghe, Kremlin; Rayner, Mike; Goldacre, Michael; Townsend, Nick; Scarborough, Peter
Abstract : Objectives: The aim of this modelling study was to estimate the expected changes in the nutritional quality and greenhouse gas emissions (GHGEs) of primary school meals due to the adoption of new mandatory food-based standards for school meals. Setting: Nationally representative random sample of 136 primary schools in England was selected for the Primary School Food Survey (PSFS) with 50% response rate. Participants: A sample of 6690 primary students from PSFS who consumed school meals. Outcome measures: Primary School Food Plan (SFP) nutritional impact was assessed using both macronutrient and micronutrient quality. The environmental impact was measured by GHGEs. Methods: The scenario tested was one in which every meal served in schools met more than half of the food-based standards mentioned in the SFP (SFP scenario). We used findings from a systematic review to assign GHGE values for each food item in the data set. The GHGE value and nutritional quality of SFP scenario meals was compared with the average primary school meal in the total PSFS data set (pre-SFP scenario). Prior to introduction of the SFP (pre-SFP scenario), the primary school meals had mandatory nutrient-based guidelines. Results: The percentage of meals that met the protein standard increased in the SFP scenario and the proportion of meals that met the standards for important micronutrients (eg, iron, calcium, vitamin A and C) also increased. However, the SFP scenario did not improve the salt, saturated fat and free sugar levels. The mean GHGE value of meals which met the SFP standards was 0.79 (95% CI 0.77 to 0.81) kgCO2 e compared with a mean value of 0.72 (0.71 to 0.74) kgCO2 e for all meals. Adopting the SFP would increase the total emissions associated with primary school meals by 22 000 000 kgCO2 e per year. Conclusions: The universal adoption of the new food-based standards, without reformulation would result in an increase in the GHGEs of school meals and improve some aspects of the nutritional quality, but it would not improve the average salt, sugar and saturated fat content levels.